Determinantes do desempenho dos veículos de investimento de private equity e venture capital: evidências do caso brasileiro - Siqueira, Eduardo Madureira Rodrigues (2008)
This paper investigates the influence of the characteristics of private equity and venture capital (PE/VC) organizations on the performance of their funds. Specifically, the analysis seeks to detect how the profiles of investment vehicles, managers and investors determine the success of the portfolio’s companies exits. The study uses a database of PE/VC from FGVEAESP, collected in the First Brazilian Census of Private Equity and Venture Capital and the Guide GVcepe-Endeavor. The sample used in the analyses is composed of 63 investment vehicles that performed at least one exit, between 1999 and the end of the first semester of 2007. The percentage and the number of disinvestment made by initial public offerings (IPO), trade sale or secondary sale in the exits of the fund were used as measures of performance of the investment vehicles. According to the related literature, these mechanisms of disinvestment are the most efficient and profit means of liquidation of the private equity and venture capital participation in a portfolio company. The main findings indicate that only the investment vehicles and managers characteristics influence the success in the exits of PE/VC funds in Brazil, showing that the Smart Money doesn’t exist for the Brazilian PE/VC industry. Therefore, the evidences found lead to the conclusion that it is not possible to assure that some investors have the ability to identify the best managers, investing with them and than achieve better performance. The results of this study are robust and are consistent with the theory and the assumptions expected. Among the evidence found in the analysis, be highlighted that the following characteristics of the PE/VC organizations significantly affect the performance of investment vehicles: amount of committed capital, number of investments already made, the level of control of managers in the invested companies, the co-investments made, the presence of investors in investment committees, foreign origin of the PE/VC organization, focus on private equity firms, the percentage of selection of investments, intensity of contact between managers and companies in the portfolio and experience of the management team in the PE/VC industry.